AUTOMATION SINGLE AXIS TYPE OF ACTIVE SYSTEM TRACKING ON PHOTOVOLTAIC - Deny Suryana (Widyariset, 2016)
Power generation from photovoltaic (PV) power is affected by radiation intensity of the sun and temperature of the environment. PV can produce maximum power when its position to the sun is optimum. The objective of this research is to control PV position toward the sun by using an active tracking system in order to produce optimum electric power. Two Light DependentResistor (LDR) sensors were placed on the east and west side of the PV, and a balance was placed in between. When the sun is on the east side from 7 a.m to 11 a.m the east LDR was exposed to light, while the west LDR was covered by balancer. When the sun is on the west side from 1 p.m to 5 p.m, west LDR was exposed to the light, while the east LDR was covered by balancer. The light intensity difference that is received by each LDR showed that an active tracking system would conduct a control action to PV position so that it will be perpendicular to the sun. The testing result showed that the difference of maximum power was 39,88 watt. It also showed that the active tracking system with single axis type could become a reference for maximum solar utilization.